2013
DOI: 10.1111/anae.12291
|View full text |Cite
|
Sign up to set email alerts
|

Reaction time‐monitored patient‐maintained propofol sedation: a pilot study in oral surgery patients

Abstract: SummaryPrevious volunteer studies of an effect-site controlled patient-maintained sedation system using propofol have demonstrated a risk of oversedation. We have incorporated a reaction time monitor into the handset to add an individualised patient-feedback mechanism. This pilot study assessed if the reaction time-feedback modification would prove safe and effective in 20 healthy patients receiving sedation while undergoing oral surgery. All patients successfully sedated themselves without reaching any unsafe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…PMPS has been examined in four healthy volunteer studies (a total of 70 participants), 10,12,18,21 nine observational clinical studies (251 participants), 9,11,13,15,17,19,22,23 and three prospective RCTs (150 participants). 15,17,20 One RCT protocol, published by the authors of this review, comparing PMPS with anaesthetist-controlled propofol sedation in lower limb arthroplasty surgery was identified.…”
Section: Population and Clinical Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…PMPS has been examined in four healthy volunteer studies (a total of 70 participants), 10,12,18,21 nine observational clinical studies (251 participants), 9,11,13,15,17,19,22,23 and three prospective RCTs (150 participants). 15,17,20 One RCT protocol, published by the authors of this review, comparing PMPS with anaesthetist-controlled propofol sedation in lower limb arthroplasty surgery was identified.…”
Section: Population and Clinical Settingsmentioning
confidence: 99%
“…24 The studies identified have taken place in the setting of general surgery, 17 orthopaedic surgery, 17,23 endoscopic retrograde cholangiopancreatography (ERCP), 11 colonoscopy, 15,20 and oral surgery. 13,14,16,17,19,22 Table 2 Pharmacokinetic models and sedation algorithms used in published studies. Terms are defined as follows: Starting concentration, the concentration of propofol at which participants commence the sedation regime; Increment concentration, the increase applied to the target-site concentration of propofol obtained by each participant handheld trigger activation; Lock-out time, the time after an increment in target-site concentration during which a subsequent handheld trigger activation will not cause a further increment; Maximum obtainable concentration, the 'ceiling' target-site concentration, above which the sedation will not increment regardless of handheld trigger activations; Decrement concentration, the targetsite concentration reduction which is automatically applied in the event of no handheld trigger activations within the decrement time; Decrement time, the time which must expire with no handheld trigger activations before the decrement concentration is automatically applied; Minimum concentration, the target-site concentration below which the sedation will not decrement during the sedation period.…”
Section: Population and Clinical Settingsmentioning
confidence: 99%
See 1 more Smart Citation